A People's Constitution: The Everyday Life of Law in the Indian Republic: How to Write New Constitutional Histories? The Casebook of Everyday Life. Issue 2 (December 2020) - DE, Rohit
Abstract : I am grateful to Professor Mathew John for his deep and rigorous engagement with A People's Constitution: The Everyday Life of Law in the Indian Republic, and to the editors of this journal for giving me the opportunity to be in dialogue with some of the questions he raises.